Prognosos of HIV-infection progression and the search for the predictors of aids and pulmonary tuberculosis development - Koval, Tetiana; Dubynska, Galyna (ScienceRise: Medical Science, 2017)
HIV-infection is the most urgent problem of health protection because of the high morbidity level, polymorphism of clinical manifestations, high risk of the unfavorable results development and significant economic losses, caused by the prevalence of persons of working age among infected people. But factors that favor the pulmonary tuberculosis development in HIV-infected patients remain unexplained and need separate studies. Aim of the research – to increase the prognostication of HIV-infection course based on determining predictors of progression to AIDS stage and pulmonary tuberculosis development. Materials and methods. The retrospective cohort analysis of 1498 HIV-infected patients, among which 491 had IV clinical stage of HIV-infection during the observation period (2003–2015, was realized. The statistical analysis was realized using Cox regression. Results of the research. At the analysis of predictors of HIV-infection progression to ІV clinical stage the binary analysis revealed five important ones: male sex (HR=0,644, 95 %CI [0,518-0,800], р=0,000), patients’ age (HR=1,016, 95 %CI [1,002-1,029], р=0,022), infection duration >3 years (HR=1,252, 95 %CI [1,200-1,306], р=0,000), initial level of СD4 lymphocytes less than 350 cells/mcl (HR=0,997, 95 %CI [0,996-0,998], р=0,000) and parenteral way of HIV transmission (HR=1,478, 95 %CI [1,090-2,004], р=0,012). The multiple analysis of Cox proportional intensities determined independent predictors of HIV-infection progression to ІV clinical stage as: male sex (HR=0,627, р=0,000), infection duration >3 years (HR=1,222, р=0,000), parenteral way of HIV-infection transmission (HR=0,627, р=0,000), and primary level of СD4 lymphocytes < 350 cells/mcl (HR=0,997, р=0,000). The independent predictors of the pulmonary tuberculosis development in HIV-infected patients were determined as: male sex (HR=0,517, р=0,000), presence of VHC-co-infection (HR=0,433, р=0,000) and HIV-infection duration > 3 years (HR=1,177, р=0,000). Conclusions: 1. The independent predictors of HIV-infection progression to ІV clinical stage as: male sex infection duration >3 years parenteral way of HIV-infection transmission and primary level of СD4 lymphocytes < 350 cells/mcl. 2. The independent predictors of the pulmonary tuberculosis development in HIV-infected patients were determined as: male sex presence of VHC-co-infection and HIV-infection duration > 3 years